1998
DOI: 10.1002/(sici)1097-4644(19980601)69:3<244::aid-jcb2>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the 67-kDa laminin receptor by acylation of the precursor

Abstract: Even though the involvement of the 67-kDa laminin receptor (67LR) in tumor invasiveness has been clearly demonstrated, its molecular structure remains an open problem, since only a full-length gene encoding a 37-kDa precursor protein (37LRP) has been isolated so far. A pool of recently obtained monoclonal antibodies directed against the recombinant 37LRP molecule was used to investigate the processing that leads to the formation of the 67-kDa molecule. In soluble extracts of A431 human carcinoma cells, these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
110
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 23 publications
6
110
0
2
Order By: Relevance
“…Our data strongly support a physiological role of the laminin receptor/The polypeptide predicted from the non-integrin laminin receptor cDNA sequence consists of 295 amino acids and the in vitro translation of selectively hybridized mRNA produced a protein with an apparent molecular mass of 37 kDa on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (Rao et al, 1989). However, other isoforms of the laminin receptor, displaying higher molecular masses, have also been described (Castronovo et al, 1991;Landowski et al, 1995;Menard et al, 1997;Buto et al, 1998). One of these isoforms, the 67 kDa high affinity laminin receptor (LR: presumably the mature form of the receptor), is thought to arise from the heterodimerization of its precursor molecule, the 37 kDa LRP, with a still unidentified molecule (Buto et al, 1998).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Our data strongly support a physiological role of the laminin receptor/The polypeptide predicted from the non-integrin laminin receptor cDNA sequence consists of 295 amino acids and the in vitro translation of selectively hybridized mRNA produced a protein with an apparent molecular mass of 37 kDa on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (Rao et al, 1989). However, other isoforms of the laminin receptor, displaying higher molecular masses, have also been described (Castronovo et al, 1991;Landowski et al, 1995;Menard et al, 1997;Buto et al, 1998). One of these isoforms, the 67 kDa high affinity laminin receptor (LR: presumably the mature form of the receptor), is thought to arise from the heterodimerization of its precursor molecule, the 37 kDa LRP, with a still unidentified molecule (Buto et al, 1998).…”
mentioning
confidence: 80%
“…However, other isoforms of the laminin receptor, displaying higher molecular masses, have also been described (Castronovo et al, 1991;Landowski et al, 1995;Menard et al, 1997;Buto et al, 1998). One of these isoforms, the 67 kDa high affinity laminin receptor (LR: presumably the mature form of the receptor), is thought to arise from the heterodimerization of its precursor molecule, the 37 kDa LRP, with a still unidentified molecule (Buto et al, 1998). The 67 kDa LR is believed to be the functional isoform of the receptor regarding its ability to mediate strong attachement of cells to laminin (Lesot et al, 1983;Malinoff and Wicha, 1983;Rao et al, 1983), to be overexpressed on cancer cell sufaces, and to promote the invasive and metastatic capacity of these cells (Menard et al, 1997).…”
mentioning
confidence: 99%
“…Although LR has no obvious signal peptide and precursor of LR remained in cytoplasm as a component of the translational machinery [39], cell surface association of mature LR has been well documented [40,41]. It is unclear how the 37 kD precursor is converted to the 67 kD LR, although it has been suggested that it is due to either homo or heterodimerization of the 37 kD LR [21,22]. Regardless, in the membrane bound state, the C-terminal two-thirds of the LR is located extracellularly and contains a 6 amino acid laminin-binding sequence, whereas the N-terminal third faces the cytoplasm preceded by a short transmembrane domain [40].…”
Section: Discussionmentioning
confidence: 99%
“…The two cleavage sites by ST3 are indicated by two arrows. LR is either a homodimer of the 37 kD or a heterodimer with another protein [21,22]. Only the 37 kD precursor protein (referred here and in the text simply as LR) is shown here for simplicity.…”
Section: Identification Of Laminin Receptor (Lr) As a Putative Substrmentioning
confidence: 99%
See 1 more Smart Citation